2021
DOI: 10.1055/s-0041-1727274
|View full text |Cite
|
Sign up to set email alerts
|

Speech Recognition in Noise Using Binaural Diotic and Antiphasic Digits-in-Noise in Children: Maturation and Self-Test Validity

Abstract: Background Digits-in-noise (DIN) tests have become popular for hearing screening over the past 15 years. Several recent studies have highlighted the potential utility of DIN as a school-aged hearing test. However, age may influence test performance in children due to maturation. In addition, a new antiphasic stimulus paradigm has been introduced, allowing binaural intelligibility level difference (BILD) to be measured by using a combination of conventional diotic and antiphasic DIN. Purpose This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 58 publications
4
15
0
Order By: Relevance
“…Moreover, the SRT-values of the antiphasic procedure did not seem to be stable after a training phase with 21 trials, and a training effect seemed to be present between the first and the second antiphasic test. When looking into other research that uses SPIN tests with dichotic stimuli, no reports could be found about the training time needed for a dichotic test ( de Sousa et al, 2020 ; Smits et al, 2016 ; Wolmarans et al, 2021 ). However, a complete second training phase would increase the test by around 1 min, leaving the test duration at around 5 min, similar to the duration of the reference procedure with monaurally tested ears.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the SRT-values of the antiphasic procedure did not seem to be stable after a training phase with 21 trials, and a training effect seemed to be present between the first and the second antiphasic test. When looking into other research that uses SPIN tests with dichotic stimuli, no reports could be found about the training time needed for a dichotic test ( de Sousa et al, 2020 ; Smits et al, 2016 ; Wolmarans et al, 2021 ). However, a complete second training phase would increase the test by around 1 min, leaving the test duration at around 5 min, similar to the duration of the reference procedure with monaurally tested ears.…”
Section: Methodsmentioning
confidence: 99%
“…Childhood hearing screening programs could also benefit from this approach, considering that CHL linked with otitis media is more prevalent among children than adults. The simple test paradigm using familiar digits-in DIN tests allows for reliable responses in children as young as four years (Koopmans et al 2018; Wolmarans et al 2021), although young children may need an adult to facilitate the test procedure. Furthermore, suprathreshold testing provides the benefit of being less sensitive to ambient noise as school age-hearing screening is typically conducted outside a soundproof booth.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, Wolmarans et al. (2021) used a digits-in-noise test implemented on a smartphone to test ∼600 school-going children aged 6–14 years with average hearing thresholds of ≤20 dB HL (calculated across 1, 2, and 4 kHz and left and right ears).…”
Section: Introductionmentioning
confidence: 99%